Challenges and Opportunities in the Inbound Tourism of Japan After Disaster and Pandemic - Paidi, Rohayati; Suki, Mohd Najmuddin; Md Akhir, Md Nasrudin; Govindasamy, Geetha; Abdul Halim, Siti Fatimah (WILAYAH: The International Journal of East Asian Studies, 2021)
According to the data published by JTB Tourism Research & Consulting Co., for the period beginning 1990 until 2019, the growth rate of inbound tourism in Japan has shown a steady increase which resulted in an average of 11.5% every year. This encouraging development was the result of the full-fledged ‘‘Inbound Tourism Initiative’’ campaign launched in 2003, which originally aimed at attracting 10 million foreign tourists to Japan in 2010. However, it is undeniable that there were so many challenges Japan had to overcome alongside that process due to problems that arise out of things beyond control such as natural disasters and epidemics. This article discusses in detail the volatile situation plaguing the inbound tourism industry in Japan. Analyzing from one single perspective that is why people would or would not travel to Japan, this paper seeks to observe how Japan managed to realize the inbound tourism rebound after disasters and epidemics. By employing secondary data analysis, this effort aims to present data about the determinants and factors influencing inbound tourism to Japan from as many countries as possible. This work will then examine in depth the challenges and opportunities that Japan might need to deal with in addressing the impact of COVID-19 on inbound tourism by taking Malaysia as a case study.